The Impact of Trust and Service Quality on Consumer Loyalty at Royal Holiday - Muammar Rinaldi; Ihsan Effendi (LPPM STIE EKA PRASETYA, 2021)
This study aims to determine the effect of Trust and Service Quality on Consumer Loyalty on Royal holidays. The population in this study are all consumers who make purchases on Royal Holiday as many as 135 consumers. By using the Slovin formula with an error rate of 5%, a total sample of 101 respondents was obtained. The results of the research analysis showed that Trust and Service Quality partially have a positive and significant effect on Consumer Loyalty on Royal holidays. The results showed that Trust and Service Quality simultaneously have a positive and significant effect on Consumer Loyalty in Royal holidays. The results of this study are supported by the value of R square (R2) which means that Trust and Service Quality have an effect on Consumer Loyalty on Royal holidays. While the remaining is affected by other factors originating from outside this research model such as price, commitment, image, location, discounted price, advertising, and consumer behavior